Public Response to COVID-19 in the Media: Are You Anxious or in Awe? - Zainal, Asliah; binti Awad, Faizah; Kina, Wa; Atikah, Dewi (KnE Social Sciences, 2022)
People today are more disoriented as a result of COVID-19. People are often confused as a result of the abundance of information provided by all forms of offline and online media. The purpose of this paper was to look at how people reacted to the government’s handling of COVID-19 in the media. Data were gathered from social media and television content that depicted the public’s reactions and attitudes toward the government’s COVID-19 handling policy. After that, the data were analyzed using an interpretive approach. The findings revealed three distinct types of public reactions: anxiety, awe, and silliness. People were more likely to experience anxiety, fear and panic, as well as panic buying, spreading hoaxes, refusing to have rapid tests or PCR tests, isolating themselves, and avoiding medical personnel. Some people, on the other hand, reacted by displaying positive messages, positive support, and humor. Also, others indicated that they would do things like forge signatures, flee the hospital/isolation room, confiscate and dismantle coffins, be desperate to break health protocols, travel and vacation while ignoring risks, and try to influence the officers when they returned home. The three types of responses of anxiety, awe and ridiculousness highlighted different people’s awareness and knowledge of COVID-19. Keywords: COVID-19, pandemic, new media, anxious, awe, ridiculous or silly, literate